Three-dimensional carbon nitride photocatalyst with tip structure as well as preparation method and application of three-dimensional carbon nitride photocatalyst

The graphite phase carbon nitride was synthesized by heat condensation method, and in situ polymerization and high-temperature molten salt calcination were formed in polyphenol solution to form a three-dimensional carbon nitride photocatalyst with a cutting-edge structure, solving the problem of insufficient activity and stability of traditional g-C3N4 photocatalysts, and achieving efficient and stable photocatalytic decomposition of aquatic hydrogen.

CN119524906AActive Publication Date: 2025-02-28NANCHANG UNIV

Patent Information

Application Number
CN202411714206.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The traditional graphite phase carbon nitride (g-C3N4) photocatalyst is prepared by one-step heat condensation method, which has problems such as poor mass transfer, small specific surface area, and low carrier recombination rate, which limits its photocatalytic activity and stability.

Method used

The graphite phase carbon nitride is synthesized by heat condensation method, and polymerized in situ in the polyphenol solution to form a polypolyphenol coating, which is then mixed with the molten salt and calcined at high temperature to form a three-dimensional carbon nitride photocatalyst with a tip structure.

Benefits of technology

The obtained three-dimensional carbon nitride photocatalyst has extremely high photocatalytic decomposition of aquatic hydrogen activity and stability under normal temperature and pressure. The preparation method is green and environmentally friendly, the raw materials are simple and easy to obtain, and has good application prospects and economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524906A_ABST
    Figure CN119524906A_ABST
Patent Text Reader

Abstract

The invention provides a three-dimensional carbon nitride photocatalyst with a tip structure as well as a preparation method and application of the three-dimensional carbon nitride photocatalyst, and relates to the technical field of photocatalysts. The preparation method provided by the invention comprises the following steps: performing thermal condensation polymerization on a nitrogen-rich precursor to obtain graphite-phase carbon nitride; the preparation method comprises the following steps: mixing graphite phase carbon nitride in a polyphenol solution, dropwise adding a Tris-HCl solution, carrying out stirring reaction, carrying out in-situ polymerization on polyphenol on the surface of the graphite phase carbon nitride to form a polypolyphenol coating, and carrying out separation and drying to obtain a composite intermediate; and mixing and grinding the composite intermediate and fused salt, and calcining in a protective atmosphere of 400-650 DEG C to obtain the three-dimensional carbon nitride photocatalyst with a tip structure. The preparation method provided by the invention is green and environment-friendly, the raw materials are simple, convenient, easy to obtain and low in price, meanwhile, the reaction conditions are mild, a template agent does not need to be used, and the prepared catalyst has a tip structure, has extremely high activity of photocatalytic decomposition of water to produce hydrogen and excellent stability at normal temperature and normal pressure, and has good application prospects and economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photocatalysts, and in particular to a three-dimensional carbon nitride photocatalyst with a tip structure, and a preparation method and application thereof. Background Art

[0002] Hydrogen energy is expected to become an ideal energy source to replace fossil fuels due to its high calorific value and pollution-free combustion products. Using solar energy to photocatalytically decompose water to produce hydrogen, low-density solar energy can be converted into high-density chemical energy and stored in hydrogen through suitable photocatalysts, which has broad application prospects. Therefore, the development of an efficient and stable photocatalytic material is the current research focus. Graphitic carbon nitride (g-C3N4), as a metal-free organic polymer photocatalyst, has become a research hotspot due to its unique electronic structure, good physical and chemical stability, and easy regulation.

[0003] The g-C3N4 prepared by the traditional one-step thermal polycondensation method is easy to form blocks due to poor mass transfer, resulting in shortcomings such as small specific surface area and high carrier recombination rate, which limits the photocatalytic activity of g-C3N4. Constructing g-C3N4 with a cutting-edge structure can not only promote light collection, but also accelerate charge collection and promote interfacial charge transfer. At the same time, the introduction of carbon-based materials in g-C3N4 can further promote charge transfer, adjust the band structure of g-C3N4, and improve light response. However, since carbon materials are generally introduced by copolymerization of carbon sources, this is likely to form amorphous carbon inside g-C3N4 or destroy the framework structure of g-C3N4, and the direct thermal polycondensation method is incompletely polycondensed and easily introduces defects, thereby reducing the activity of the photocatalytic reaction. Therefore, a solution is urgently needed to improve the above problems. Summary of the invention

[0004] The purpose of the present invention is to provide a three-dimensional carbon nitride photocatalyst with a cutting-edge structure and a preparation method and application thereof. The preparation method is green and environmentally friendly, the raw materials are simple, easy to obtain and inexpensive, and the reaction conditions are mild and no template agent is required. The prepared catalyst has a cutting-edge structure and has extremely high photocatalytic water decomposition and hydrogen production activity and stability at room temperature and pressure, and has good application prospects and economic benefits.

[0005] In a first aspect, the present invention provides a method for preparing a three-dimensional carbon nitride photocatalyst with a pointed structure, comprising: preparing a graphite phase carbon nitride by thermal polycondensation of a nitrogen-rich precursor; mixing the graphite phase carbon nitride in a polyphenol solution, adding a Tris-HCl solution dropwise and stirring the mixture to polymerize the polyphenol on the surface of the graphite phase carbon nitride in situ to form a polyphenol coating, and separating and drying the mixture to obtain a composite intermediate; mixing and grinding the composite intermediate with a molten salt, and calcining the mixture at 400-650°C in a protective atmosphere to obtain a three-dimensional carbon nitride photocatalyst with a pointed structure.

[0006] The preparation method provided by the present invention is green and environmentally friendly, the raw materials are simple, easily available and inexpensive, and the reaction conditions are mild without the need for a template. The prepared photocatalyst has extremely high photocatalytic reaction activity and long-term catalytic stability, and has good application prospects and economic benefits.

[0007] Optionally, the nitrogen-rich precursor includes one of melamine, dicyandiamide, urea and thiourea.

[0008] Optionally, the nitrogen-rich precursor is calcined at 400-650° C. in an inert atmosphere.

[0009] Optionally, the nitrogen-rich precursor is subjected to thermal polycondensation under an inert atmosphere for 2-10 hours.

[0010] Optionally, the mass ratio of the polyphenol solute in the polyphenol solution to the graphite-phase carbon nitride is 1:(5-200).

[0011] Optionally, the polyphenol solute in the polyphenol solution includes one of tannic acid, dopamine and gallic acid.

[0012] Optionally, the concentration of the Tris-HCl solution is 0.1-5.0 mol / L.

[0013] Optionally, the pH of the Tris-HCl solution is 8.5.

[0014] Optionally, the molten salt includes one of KCl-LiCl, KCl-NaCl, and KCl-NaCl-LiCl.

[0015] Optionally, the mass ratio of the composite intermediate to the molten salt is 1:(2-10).

[0016] Optionally, the protective atmosphere includes one of a nitrogen atmosphere and an argon atmosphere.

[0017] Optionally, calcining is performed at 400-650° C. under protective atmosphere for 2-10 h.

[0018] In a second aspect, the present invention also provides a three-dimensional carbon nitride photocatalyst with a tip structure obtained by any of the above optional preparation methods.

[0019] In a third aspect, the present invention also provides the use of a three-dimensional carbon nitride photocatalyst with a tip structure prepared by any of the above optional preparation methods in photocatalytic decomposition of water to produce hydrogen. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 A flow chart of a method for preparing a three-dimensional carbon nitride photocatalyst with a tip structure provided by the present invention;

[0021] Figure 2 A bar graph showing the hydrogen production rate of the three-dimensional carbon nitride photocatalyst prepared in Examples 1 to 4 and Comparative Example 1 of the present invention during the photocatalytic water hydrogen production reaction;

[0022] Figure 3 A bar graph showing the hydrogen production rate of the three-dimensional carbon nitride photocatalysts prepared in Examples 3, 5 to 7 of the present invention during the photocatalytic water hydrogen production reaction;

[0023] Figure 4 This is a SEM characterization image of the three-dimensional carbon nitride photocatalyst prepared in Example 3 of the present invention;

[0024] Figure 5 This is a TEM characterization image of the three-dimensional carbon nitride photocatalyst prepared in Example 3 of the present invention;

[0025] Figure 6 This is a graph showing the change in hydrogen production of the three-dimensional carbon nitride photocatalyst prepared in Example 3 of the present invention during photocatalytic hydrogen production;

[0026] Figure 7 This is a comparison diagram of XRD characterization of the three-dimensional carbon nitride photocatalyst prepared in Example 3 of the present invention before and after photocatalytic hydrogen production. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.

[0028] See also Figure 1 The present invention provides a method for preparing a three-dimensional carbon nitride photocatalyst with a tip structure, comprising:

[0029] S1, thermally condense a nitrogen-rich precursor to obtain graphite carbon nitride;

[0030] S2, mixing graphite phase carbon nitride in a polyphenol solution, adding Tris-HCl solution dropwise, stirring for reaction, separating and drying to obtain a composite intermediate;

[0031] S3. The composite intermediate is mixed with molten salt and ground, and calcined at 400-650° C. in a protective atmosphere to obtain a three-dimensional carbon nitride photocatalyst.

[0032] In fact, the present invention synthesizes graphite phase carbon nitride by thermal polycondensation, and forms a polyphenol coating by in situ polymerization of polyphenols on the surface of graphite phase carbon nitride, and further etches it with high-temperature molten salt to obtain a three-dimensional carbon nitride photocatalyst with a cutting-edge structure, which has high photocatalytic reaction activity and good cycle stability.

[0033] In fact, after mixing polyphenols with graphite phase carbon nitride, polyphenols react with amino groups on the surface of graphite phase carbon nitride through functional groups such as hydroxyl groups, and undergo in situ polymerization on the surface of graphite phase carbon nitride. At the same time, creating a fluid environment through high-temperature molten salt can effectively promote mass transfer, and the high-temperature molten salt environment promotes the polyphenol coating to form an expanded carbonized polyphenol coating. In addition, the molten salt fluid enters the carbonized expanded polyphenol coating and selectively etches the graphite phase carbon nitride, which can effectively regulate the morphology of the photocatalyst, thereby increasing the active sites of the photocatalyst.

[0034] In some embodiments, the nitrogen-rich precursor used in step S1 includes one of melamine, dicyandiamide, urea, and thiourea. In addition, in step S1, the nitrogen-rich precursor is calcined in an inert atmosphere at 400-650° C. for 2-10 hours, which is beneficial to improve the thermal polycondensation effect.

[0035] In a further embodiment, in step S1, the nitrogen-rich precursor can be placed in a tube furnace, and after the gas in the tube furnace is replaced with an inert atmosphere, the nitrogen-rich precursor is heated to 400-650°C at a rate of 1-10°C / min and kept warm for 2-10h.

[0036] In some embodiments, in step S2, the mass ratio of the polyphenol solute to the graphite phase carbon nitride in the polyphenol solution is 1: (5-200), and the polyphenol solute in the polyphenol solution includes one of tannic acid, dopamine, and gallic acid. In fact, by selecting different polyphenols, different polyphenol layers can be polymerized on the surface of the graphite phase carbon nitride, and the thickness of the polyphenol layer can be controlled by controlling the amount of polyphenol added and the polymerization time, and then the expanded carbonized polyphenol layer is obtained after carbonization in the molten salt.

[0037] In some embodiments, the concentration of the Tris-HCl solution used in step S2 is 0.1-5.0 mol / L, and the pH of the Tris-HCl solution is 8.5. In fact, the thickness of the formed polyphenol coating is controlled by adding the Tris-HCl solution drop by drop into the mixture of graphite phase carbon nitride and polyphenol solution, and controlling the dripping time of the Tris-HCl solution. Specifically, the total dripping time of Tris-HCl can be 15-120 min.

[0038] In some embodiments, the molten salt used in step S3 includes one of KCl-LiCl, KCl-NaCl, and KCl-NaCl-LiCl. In addition, the mass ratio of the composite intermediate to the molten salt is 1:(2-10), and the protective atmosphere used is one of nitrogen atmosphere and argon atmosphere. In some embodiments, in step S3, calcination is carried out under a protective atmosphere at 400-650°C for 2-10h.

[0039] Example 1

[0040] This embodiment 1 provides a method for preparing a three-dimensional carbon nitride photocatalyst with a tip structure, comprising the following steps:

[0041] S1. 2 g of melamine was placed in the furnace of a tube furnace and nitrogen was introduced for gas replacement. The temperature of the tube furnace was raised to 550° C. at a rate of 10° C. / min and kept at this temperature for calcination for 2 h. After cooling to room temperature, the melamine was taken out and ground to obtain graphite phase carbon nitride.

[0042] S2, dissolving 3 mg of tannic acid in 70 mL of deionized water, adding 0.3 g of graphite phase carbon nitride to the above tannic acid aqueous solution, stirring for 0.5 h to obtain a mixed suspension; dropping 10 mL of Tris-HCl solution with a pH of 8.5 and a concentration of 0.1 mol / L into the above mixed suspension dropwise, and controlling the dropping time to be 60 min; stirring continuously while dropping the Tris-HCl solution; after the dropping is completed, filtering and separating, washing with deionized water, and drying in an oven at 60 ° C for 12 h to obtain a composite intermediate;

[0043] S3. The composite intermediate and molten salt (2.25 times the mass ratio of KCl and 2.75 times the mass ratio of LiCl to the composite intermediate) were mixed and ground evenly, and then transferred to a tubular furnace. After calcining at 550°C for 2 h in a nitrogen atmosphere, the mixture was cooled to room temperature with the furnace and taken out. After washing with deionized water, the mixture was dried in an oven at 60°C for 12 h to obtain a three-dimensional carbon nitride-based photocatalyst (TCS-1).

[0044] Example 2

[0045] This Example 2 provides a method for preparing a three-dimensional carbon nitride photocatalyst with a pointed structure. The difference from Example 1 is that in step S2, 6 mg of tannic acid is dissolved in 70 mL of deionized water, and the dripping time of the Tris-HCl solution is controlled to be 60 min, and a three-dimensional carbon nitride-based photocatalyst (TCS-2) is prepared in S4.

[0046] Example 3

[0047] This Example 3 provides a method for preparing a three-dimensional carbon nitride photocatalyst with a pointed structure. The difference from Example 1 is that in step S2, 12 mg of tannic acid is dissolved in 70 mL of deionized water, and the dripping time of the Tris-HCl solution is controlled to be 60 min, and a three-dimensional carbon nitride-based photocatalyst (TCS-4) is prepared in S4.

[0048] Example 4

[0049] This Example 4 provides a method for preparing a three-dimensional carbon nitride photocatalyst with a pointed structure. The difference from Example 1 is that in step S2, 24 mg of tannic acid is dissolved in 70 mL of deionized water, and the dripping time of the Tris-HCl solution is controlled to be 60 min, and a three-dimensional carbon nitride-based photocatalyst (TCS-8) ​​is prepared in S4.

[0050] Comparative Example 1

[0051] This comparative example 1 provides a method for preparing a three-dimensional carbon nitride photocatalyst with a pointed structure, which is different from Example 1 in that tannic acid is not added in step S2, but 0.3 g of graphite phase carbon nitride is used in step S3 to prepare a three-dimensional carbon nitride-based photocatalyst (TCS-0).

[0052] Performance Testing

[0053] The three-dimensional carbon nitride photocatalysts prepared in Examples 1 to 4 and Comparative Example 1 were subjected to a photocatalytic decomposition of water to produce hydrogen, comprising the following steps: 50 mg of the photocatalyst was uniformly dispersed in an aqueous solution of triethanolamine with a volume fraction of 10%, and then 4 mL of chloroplatinic acid solution was added to make the volume 100 mL, and after ultrasonic dispersion for 5 minutes, nitrogen was bubbled for 30 minutes to remove oxygen in the reaction environment, a xenon lamp with a power of 300 W was used as a light source for irradiation in the visible light range, and continuous stirring was maintained during the reaction, and the hydrogen production rate was calculated using a gas chromatograph (TCD detector, nitrogen as a carrier gas), and the results are as follows Figure 2 shown.

[0054] from Figure 2 It can be seen that the photocatalysts prepared in Examples 1 to 4 of the present invention have good catalytic activity, and the hydrogen production rate is 10-12 mmol / g·h. At the same time, compared with Comparative Example 1, it can be seen that by using tannic acid to perform polymerization carbonization on the surface of graphite phase carbon nitride, and further forming a morphology with a three-dimensional tip structure by molten salt etching, the photocatalytic activity of the photocatalyst is significantly increased. At the same time, it can be seen from Examples 1 to 4 that when the mass ratio of tannic acid to graphite phase carbon nitride is 4%, the activity of the prepared photocatalyst is good.

[0055] Example 5

[0056] This embodiment 5 provides a method for preparing a three-dimensional carbon nitride photocatalyst with a pointed structure, which is different from embodiment 3 in that the dripping time of the Tris-HCl solution in step S2 is 30 minutes.

[0057] Example 6

[0058] This Example 6 provides a method for preparing a three-dimensional carbon nitride photocatalyst with a pointed structure, which is different from Example 3 in that the dripping time of the Tris-HCl solution in step S2 is 90 minutes.

[0059] Example 7

[0060] This embodiment 7 provides a method for preparing a three-dimensional carbon nitride photocatalyst with a pointed structure, which is different from embodiment 3 in that the dripping time of the Tris-HCl solution in step S2 is 120 minutes.

[0061] Performance Testing

[0062] The three-dimensional carbon nitride photocatalysts prepared in Examples 3, 5 to 7 were subjected to photocatalytic water decomposition to produce hydrogen, and the hydrogen production rate was calculated as follows: Figure 3 As shown. Figure 3 It can be seen that controlling the dripping time of Tris-HCl has a significant effect on the thickness of the polytannic acid coating polymerized on the surface of graphite phase carbon nitride, thereby affecting the catalytic activity of the prepared photocatalyst.

[0063] Example 8

[0064] This Example 8 provides a method for preparing a three-dimensional carbon nitride photocatalyst with a pointed structure. The difference from Example 1 is that in step S2, 0.5 mg of dopamine is dissolved in 70 mL of deionized water, and the dripping time of the Tris-HCl solution is controlled to be 30 min, and a three-dimensional carbon nitride-based photocatalyst (DCS-0.5) is prepared in S4.

[0065] Example 9

[0066] This Example 9 provides a method for preparing a three-dimensional carbon nitride photocatalyst with a pointed structure. The difference from Example 1 is that in step S2, 1 mg of dopamine is dissolved in 70 mL of deionized water, and the dripping time of the Tris-HCl solution is controlled to be 30 min, and a three-dimensional carbon nitride-based photocatalyst (DCS-1) is prepared in S4.

[0067] Example 10

[0068] This embodiment 10 provides a method for preparing a three-dimensional carbon nitride photocatalyst with a pointed structure. The difference from embodiment 1 is that in step S2, 2 mg of dopamine is dissolved in 70 mL of deionized water, and the dripping time of the Tris-HCl solution is controlled to be 30 min, and a three-dimensional carbon nitride-based photocatalyst (DCS-2) is prepared in S4.

[0069] Embodiment 11

[0070] This Example 11 provides a method for preparing a three-dimensional carbon nitride photocatalyst with a pointed structure. The difference from Example 1 is that in step S2, 4 mg of dopamine is dissolved in 70 mL of deionized water, and the dripping time of the Tris-HCl solution is controlled to be 30 min, and a three-dimensional carbon nitride-based photocatalyst (DCS-4) is prepared in S4.

[0071] Morphological characterization

[0072] The three-dimensional carbon nitride photocatalyst (TCS-4) prepared in Example 3 was characterized by SEM and TEM, respectively. Figure 4 and Figure 5 As shown. Figure 4 As can be seen from the SEM image, TCS-4 is a three-dimensional sea urchin-like structure. Figure 5 As can be seen from the TEM image, its surface has a uniform and neatly arranged needle-punctured structure, and the needle-punctured structure is slender, which is beneficial to increasing the specific surface area and the number of surface active sites of the catalyst.

[0073] Performance Testing

[0074] The three-dimensional carbon nitride photocatalyst (TCS-4) prepared in Example 3 was tested for photocatalytic decomposition of water to produce hydrogen, and the hydrogen production per hour was detected. Four cycles of monitoring were carried out, each cycle was 4 hours, and the total was 16 hours. The change of hydrogen production in each cycle was as follows: Figure 6 As shown, XRD characterization of TCS-4 before and after the periodic photocatalytic reaction was performed. Figure 7 shown.

[0075] from Figure 6 It can be seen that the three-dimensional carbon nitride photocatalyst prepared in Example 3 exhibits excellent photocatalytic hydrogen production activity, and the catalytic activity does not decrease significantly after continuous reaction for 16 hours, which shows that the photocatalyst is a relatively stable photocatalyst that can maintain long-term photocatalytic performance. Figure 7 It can be seen that there is no obvious change in the characteristic diffraction peaks and peak positions of the catalyst before and after the 16h photocatalytic reaction, which further illustrates that the catalyst can maintain good self-structural stability during the catalytic reaction.

[0076] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.

Claims

1. A method for preparing a three-dimensional carbon nitride photocatalyst with a tip structure, characterized in that: include: Graphite phase carbon nitride is obtained by thermal polycondensation of nitrogen-rich precursors; After mixing graphite phase carbon nitride in a polyphenol solution, a Tris-HCl solution is added dropwise and stirred to make the polyphenol in situ polymerize on the surface of the graphite phase carbon nitride to form a polyphenol coating, which is then separated and dried to obtain a composite intermediate; after mixing and grinding the composite intermediate with a molten salt, the composite intermediate is calcined at 400-650° C. in a protective atmosphere to obtain a three-dimensional carbon nitride photocatalyst with a tip structure.

2. The preparation method according to claim 1, characterized in that: The nitrogen-rich precursor includes one of melamine, dicyandiamide, urea and thiourea; and / or the nitrogen-rich precursor is calcined at 400-650° C. in an inert atmosphere; and / or the nitrogen-rich precursor is thermally polycondensed in an inert atmosphere for 2-10 hours.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the polyphenol solute in the polyphenol solution to the graphite phase carbon nitride is 1:(5-200); and / or, the polyphenol solute in the polyphenol solution includes one of tannic acid, dopamine and gallic acid; and / or, the concentration of the Tris-HCl solution is 0.1-5.0 mol / L; and / or, the pH of the Tris-HCl solution is 8.

5.

4. The preparation method according to claim 1, characterized in that: The molten salt includes one of KCl-LiCl, KCl-NaCl, and KCl-NaCl-LiCl; and / or, the mass ratio of the composite intermediate to the molten salt is 1:(2-10); and / or, the protective atmosphere includes one of a nitrogen atmosphere and an argon atmosphere; and / or, calcination is carried out at 400-650° C. in a protective atmosphere for 2-10 hours.

5. A three-dimensional carbon nitride photocatalyst with a pointed structure obtained by the preparation method according to any one of claims 1 to 4.

6. Use of a three-dimensional carbon nitride photocatalyst with a pointed structure obtained by the preparation method according to any one of claims 1 to 4 in photocatalytic decomposition of water to produce hydrogen.

Citation Information

Patent Citations

  • Modified graphite phase carbon nitride photocatalyst as well as preparation method and application thereof

    CN108940344A

  • Salt-assisted synthesized multi-morphology carbon nitride as well as preparation method and application thereof

    CN112871195A

  • High-stability photo-thermal hydrogel sponge as well as preparation method and application thereof

    CN114392698A

  • Activated carbon composite material as well as preparation method and application thereof

    CN115849377A

  • Preparation method and application of homotype carbon nitride heterojunction photocatalyst

    CN116116443A

Cited By

  • Modified Ti3C2MXene composite g-C3N4 photocatalytic material as well as preparation method and application thereof

    CN122273593A